2015
DOI: 10.3109/03630269.2015.1040887
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis ofα0-Thalassemia Through Urine DNA: A Novel DNA Source to Facilitate Prevention Programs in Remote Geographical Areas

Abstract: We assessed whether urinary DNA sediment was a feasible sample type for the molecular diagnosis of α-thalassemia (α-thal) mutations. Urine samples (5-10 mL) were collected from 218 male and female volunteers. The cells were centrifuged, and DNA was isolated according to the protocol of a commercial DNA isolation kit. Detection of the α(0)-thal [Southeast Asian (- -(SEA)) and - -(THAI)] deletions was performed using quantitative real-time polymerase chain reaction (q-PCR), in addition to conventional gap-PCR. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The urine sediments were able to provide the DNA for molecular diagnosis in several fields, including SEA-a thalassemia 1, as mentioned before. 12 In the study of Suwannakhon et al, however, the commercial DNA extraction kit was used to extract DNA from the urine sediment. In the present study, we attempted to apply Chelex-100 resin and heat to extract genomic DNA from urine sediments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urine sediments were able to provide the DNA for molecular diagnosis in several fields, including SEA-a thalassemia 1, as mentioned before. 12 In the study of Suwannakhon et al, however, the commercial DNA extraction kit was used to extract DNA from the urine sediment. In the present study, we attempted to apply Chelex-100 resin and heat to extract genomic DNA from urine sediments.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Ghatak et al 11 prepared the DNA from urine sediments and showed that this DNA was ready for PCR reaction. In 2015, Suwannakhon et al 12 were successful in using the urine sediment as a source of the genomic DNA for genotyping a-thalassemia 1 [Southeast Asian (SEA) type]. Recently, Ng et al 9 successfully prepared DNA from urine sediment used for Short Tandem Repeat (STR) genotyping.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 In brief, the PCR mixtures (25 µL) included 5 µl of DNA, 1X PCR buffer, 1.5 µM MgCl 2 , 200 µM of each dNTP, 2 µM of SYTO9, 1 unit of Platinum ® Taq DNA polymerase, and 0.2 µM of each primer of P1, P2, P3, TF, and TR. Thermal cycling was performed on the platform of a Bio-Rad CFX96 real-time system (Bio-Rad Laboratories, California, USA) beginning at 94°C for two minutes to activate the Taq DNA polymerase, followed by 40 cycles of denaturing at 94°C for 15 s, annealing at 64°C for 15 s, and extension at 72°C for 20 s. Fluorescence was measured on the SYBR channel (533 nm) at the end of each cycle.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%